2016
DOI: 10.18632/oncotarget.14303
|View full text |Cite
|
Sign up to set email alerts
|

Pan-organ transcriptome variation across 21 cancer types

Abstract: It is widely accepted that some messenger RNAs are evolutionarily conserved across species, both in sequence and tissue-expression specificity. To date, however, little effort has been made to exploit the transcriptome divergence between cancer and adjacent normal tissue at the pan-organ level. In this work, a transcriptome sequencing dataset from 675 normal-tumor pairs, representing 21 solid organs in The Cancer Genome Atlas, is used to evaluate expression evolution. The results show that in most cancer types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Two other studies have demonstrated that expression signatures can help classify the tissue for cancers of unknown primary origin, which presents a possible application of using the transcriptome signatures with tissue specificity in oncology (45, 46). Our work, besides adding novel knowledge to this field, corroborates studies such as that from Hu et al, which showed that in cancer, there is a decrease in the expression of some tissue-specific genes, and Pei et al, which showed that it is common for cancers to acquire specific expression profiles from other organs (47, 48).…”
Section: Discussionsupporting
confidence: 90%
“…Two other studies have demonstrated that expression signatures can help classify the tissue for cancers of unknown primary origin, which presents a possible application of using the transcriptome signatures with tissue specificity in oncology (45, 46). Our work, besides adding novel knowledge to this field, corroborates studies such as that from Hu et al, which showed that in cancer, there is a decrease in the expression of some tissue-specific genes, and Pei et al, which showed that it is common for cancers to acquire specific expression profiles from other organs (47, 48).…”
Section: Discussionsupporting
confidence: 90%
“…All level three mRNA expression datasets (RNASeqV2) were obtained from the TCGA (October 2015). Gene expression data analysis was performed similar to our previous work (12). Briefly, differentially expressed mRNA analysis between LCC and RCC was performed by the limma package for R/Bioconductor.…”
Section: Gene Expression Data Processing and Normalizationmentioning
confidence: 99%
“…Matched mRNA-miRNA samples were retained for coexpression analysis. The coexpression network was constructed by weighted correlation network analysis (WGCNA) package for R (15) and explored as in our previous work (12). The subnetworks constituted by the 50 top hub genes in the specific module were visualized by VisANT (16).…”
Section: Network Constructionmentioning
confidence: 99%
“…NFE2L2 was positively associated with immune infiltration in pan-cancer ( Ju et al, 2020b ). Pan-cancer research has allowed us to understand that the same cancer may be very different at the molecular level ( Hu et al, 2017 ), while diverse cancers may share the same molecular profile ( Comprehensive genomic cha, 2008 ). Thereby deepening the pan-cancer level studies with a large sample size will hopefully discover new biomarkers which can be used to develop new cancer treatment strategies.…”
Section: Introductionmentioning
confidence: 99%